2020 IEEE International Conference on Software Maintenance and Evolution (ICSME) 2020
DOI: 10.1109/icsme46990.2020.00056
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Test Smells in Automatically Generated Tests: Limitations, Pitfalls, and Opportunities

Abstract: Test smells attempt to capture design issues in test code that reduce their maintainability. Previous work found such smells to be highly common in automatically generated test-cases, but based this result on specific static detection rules; although these are based on the original definition of "test smells", a recent empirical study showed that developers perceive these as overly strict and non-representative of the maintainability and quality of test suites. This leads us to investigate how effective such t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…These approaches rely on detection rules that raise warnings when some metrics (e.g., size, number of method calls, number of assertions) in the test code exceed given thresholds. However, a recent study [24] showed that detection rules are far less accurate than previously reported, especially when tests use external resources.…”
Section: Related Workmentioning
confidence: 80%
“…These approaches rely on detection rules that raise warnings when some metrics (e.g., size, number of method calls, number of assertions) in the test code exceed given thresholds. However, a recent study [24] showed that detection rules are far less accurate than previously reported, especially when tests use external resources.…”
Section: Related Workmentioning
confidence: 80%
“…While our objective here is not to discredit the validity of the current set of test smell detection tools, we only highlight inconsistencies that might lead to research studies obtaining varying results based on the tool in use. As stated by Panichella et al [61], there is a need for a community-maintained gold-set/standard of smelly test files to validate the current and future smell detection tools. We understand that the process involved in the creation of a community-curated gold-set might be time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the readability of the generated tests and to avoid test smells [8], EVOSUITE applies post-processing once the available search budget has been exhausted [2,3]. In particular, minimisation is used to remove redundant tests and statements, and a minimised set of assertions is added using mutation analysis [6].…”
Section: About Evosuitementioning
confidence: 99%